Kyrgyz Republic : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria-Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kyrgyz Republic. (IMF Staff Country Reports; Country Report ;, 2012)
The Kyrgyz Republic has stabilized with the formation of a new coalition, but political uncertainty remains. Despite a slump in gold production and delays in donor financing, monetary and fiscal policies remained prudent. Improving the business climate, good governance, and strong institutions remain key to sustaining strong growth over the medium term. Fiscal consolidation with strong revenue measures and prudent expenditure policies are instrumental in safeguarding macroeconomic stability. More forceful reform efforts are needed to ensure long-term viability of the banking sector.